The ethology of foraging in ants: revisiting Tinbergen’s four questions - Lima Vieira, Maria Eduarda; Chameron, Stéphane; Châline, Nicolas (Frontiers in Ethology, 2024)
Since Tinbergen's seminal contribution in 1963, ethology has blossomed as a multifaceted research field. Sixty years later, uncountable articles followed the four questions proposed as necessary for understanding animal behaviour, and they culminated in the segmentation of subareas which communicate little among themselves. Foraging in ants is one example where this division happened, despite the clear need to integrate results obtained from different approaches.We chose this research subject to revise the literature, relating the main results to the relevant level of explanation in Tinbergen's four questions theoretical framework. Through such revision, we aim to foster the integration of different approaches and to bring to light how this can clarify how we understand foraging behaviour, sixty years after Tinbergen's initial proposition.